The Culture of Accountability A Democratic Virtue (Taylor & Francis, 2023)
This important book explores the cultural conditions that favor political accountability. It examines the channels through which accountability can be secured and the role that accountability plays in ensuring good governance. In addition to problematizing the notion of accountability, the book suggests that it is the product of three different-albeit, related-processes: taking account of voters' preferences, keeping account of voters' preferences, and giving account of one's performance in office. It further explores the relationship between accountability and political culture by analyzing the relationship between accountability and religion, religious denomination, familism, civicness, secularism, and postmaterialism, revealing that the level of accountability is influenced by the diffusion of post-material values and by the level of civicness in a given country. This book will be of key interest to scholars, students, and practitioners in governance, the political economy of institutions and development, democracy, and more broadly to political science, international relations, political theory, comparative politics, sociology, and cultural studies.
English
Keywords: Comparative politics; International relations; Politics & government; Public administration; accountability; civicness; familism; governance; political culture; postmaterialism; religious denomination; secularism